A bipolar emitting material for high efficient non-doped fluorescent organic light-emitting diode approaching standard deep blue. (June 2016) - Fan, Shigen; You, Jing; Miao, Yanqin; Wang, Hua; Bai, Qingyun; Liu, Xicheng; Li, Xianggao; Wang, Shirong
Abstract: A deep blue emitting compound 9-(4′-(1, 4, 5-triphenyl-1 H -imidazol-2-yl)-[1, 1′-biphenyl] -4-yl)-9 H -carbazole was designed and synthesized. The emitting compound characters as donor-π-acceptor structure with carbazole as the electron-donor and imidazole as the electron-acceptor. The emitting compound shows high quantum yield (0.87) in solution and good thermal stability. The emitting compound exhibits bipolar transporting characteristics identified by single-carrier devices. The non-doped fluorescent organic light-emitting diode with the emitting compound as emitting layer exhibits emission peak at 420 nm and full width at half maximum of 54 nm, maximum current efficiency of 2.30 cd/A, and maximum power efficiency of 1.52 lm/W, which are higher than most reported deep blue emitters with a y coordinate ≤0.064. The chromaticity coordinate is stable at (0.166, 0.064) with increasing operation voltage. Graphical abstract: The structure of device and EL spectra and CIE diagram at different voltages. Highlights: Reported a new deep blue emitter with high quantum yield and good thermal stability. The emitter shows good bipolar transporting characteristics. The non-doped OLED exhibits high current and power efficiency (2.30 cd/A, 1.52 lm/W).